PREDICTING POST-EXTUBATION RESPIRATORY FAILURE AFTER MYOCARDIAL INFARCTION USING THE RAPID SHALLOW BREATHING INDEX AND LUNG ULTRASOUND SCORE - Ansari, Muhammad Imran; Abubaker, Jawed; Umair, Madiha; Baloch, Komal; Karim, Musa; Salahuddin, Nawal (Journal of Ayub Medical College Abbottabad, 2022)
Background: The Rapid Shallow Breathing Index (RSBI) has been hypothesized to have discriminating power for categorizing patients at higher risk of post-extubation respiratory failure (RF). Hence aim of this study was to determine the predictive value of RSBI for post-extubation RF in patients after acute myocardial infarction (AMI). Methods: Consecutive, intubated patients admitted post-revascularization were included. RSBI and lung ultrasound score (LUS) were measured and post-extubation RF within 48 hours was recorded. Results: RF was observed in 36.3% (78/215) patients. For the prediction of RF, RSBI and LUS had area under the curve of 0.670 and 0.635, respectively. The sensitivity, specificity, negative predictive value, and positive predictive value of RSBI >50.5 were 75.6%, 54.7%, 79.8%, and 48.8% respectively, while, the accuracy measures for the combination of RSBI with LUS >1.5 were 44.9%, 84.7%, 73.0%, and 62.5% respectively. Conclusion: Combined RSBI and LUS measured during spontaneous breathing trial in patients after an AMI, have high predictive abilities for identifying post-extubation RF.